Comparison of visual acuity before and after senile cataract surgery (in patients with diabetes mellitus less than 5 years and more than 5 years) in Yogyakarta - Setyandriana, Yunani; Salsabillah, Putri Virda (Science Midwifery, 2025)
Cataract is a condition in which the lens fiber on the lens capsule crumbles. One of the complications of diabetes mellitus is diabetic retinopathy. The study aimed to compare the visual acuity before and after phacoemulsification surgery in senile cataract patients with diabetes mellitus less than and more than 5 years in Yogyakarta. It was analytical observational research with cross-sectional design. The study was conducted at the Eye Clinic of a private hospital in Yogyakarta by using samples of 53 patients. The dependent t test method was used as the research test. The results of the study were significant with a value of 0.000 (P < 0,05), indicating there was a significant correlation between the visual acuity before and after phacoemulsification.